MICROWAVE SNOW EMISSION MODEL AND ITS CONTRIBUTING PARAMETERS - Butt, Mohsin Jamil (Journal of Research (Science), 2004)
Satellites with microwave sensors onboard observing land surface from space consist of signal contributions from surface and atmosphere. The upwelling microwave signals are less attenuated by the atmosphere hence, for earthly located features remote sensing satellite microwave sensors have an advantage over visible sensor systems. In order to monitor snow cover with passive microwave data, brightness temperature information of the medium covering the earth surface under different conditions is required. A snow emission model thus, could be used for the estimation of brightness temperature of the medium. The radiative transfer based model has been used to study the emitted radiation from snow surface at the frequencies of the special sensor microwave imager (SSM/I). In the presence of clouds, water vapours and precipitation the radiative transfer calculations simplify as the wavelengths of the radiation approach the Rayleigh scattering regime. The transfer of microwave radiation, in particular is often simpler than the equivalent calculations at shorter wavelengths. This paper presents a simple sensitivity analysis of parameters used in the radiative transfer theory based snow emission model. There are several contribution factors (for example, soil, forest, water, atmosphere and snow) in the model. The effects of these features on brightness temperature values have been analysed in this paper.